2023
DOI: 10.3390/min13081045
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Viscosity-Enhancing Admixture in Backfill Slurry and the Evolution of Its Rheological Properties

Abstract: Since filling slurry is a cement-based material, viscosity-enhancing admixture exerts a significant effect on its rheological performance and mechanical properties. Viscosity-enhancing admixture can improve pipeline transportation performance and reduce pipeline wear during the filling process of a kilometer-deep mine by changing the plastic viscosity and yield stress of high-concentration filling slurries. In order to reveal the influence mechanism of viscosity-enhancing admixture on rheological performance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…From the above figure, it is observable that the compressive strength of SCSS initially decreases and subsequently increases with the augmentation of HPMC dosage, this result is consistent with the findings reported in reference [ 37 ]. Notably, the strength attains its maximum at a dosage of 0.3%.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…From the above figure, it is observable that the compressive strength of SCSS initially decreases and subsequently increases with the augmentation of HPMC dosage, this result is consistent with the findings reported in reference [ 37 ]. Notably, the strength attains its maximum at a dosage of 0.3%.…”
Section: Resultssupporting
confidence: 92%
“…Specifically, the water seepage rate for HPMC–10 settled at 0.92% finally, while HPMC–20 was even lower at 0.63%. Upon further increased the HPMC content SCSS to 0.5%, the final water seepage rates for it with two types of molecular weights of HPMC were exceptionally low in values at 0.21% and 0.22%, this is similar to the findings reported by Yang et al [ 37 ]. These results clearly demonstrated that HPMC is highly effective in reducing the water seepage rate of SCSS.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The minimum fluidity occurs in the B0.50P0.05 group, decreasing by 33.11%. The addition of BF and PANF increases the friction of tailings to promote the interlocking effect [46][47][48]. In addition, fibers also absorb some water to reduce the water film thickness (WFT) on the mortar matrix and thus further reduce the fluidity of tailing mortar [49].…”
Section: Fluidity and Densitymentioning
confidence: 99%
“…An increasingly popular green mining alternative for storing mine tailings is filling underground mines with mine tailings, which has been applied in different countries around the world [32][33][34]. A particular case to highlight is the experience acquired in Peru, the second largest producer of copper in the world, where the use of mine tailings inside underground mines is being used to avoid the generation of acid rock drainage (ARD), eliminate the emission of particulate matter and thus avoid socio-environmental impacts in hydrographic basins [35].…”
Section: The Positioning Of Mine Tailings Dewatering Technologies As ...mentioning
confidence: 99%